Let's begin a new life, consumers' response towards healthy lifestyles: do our higher education students care? / Hasnizam Shaari and Suhaila Abdul Hanan - Shaari, Hasnizam; Abdul Hanan, Suhaila (2008)
Issues on food and health are frequently making the headlines. Stories about the state of the nation's diet and the food industry's role in providing healthy choices are regularly in the news. Recent study reported that Malaysia has the most number of fat people in the Asian region, exceeding that in many developed countries, including Germany and France (MySoN, 2006). Despite the seriousness of the problem, very limited study was conducted to understand consumers' attitude towards healthy lifestyle especially in the context of Malaysia and to university students as a future asset of human capital. Therefore, this study aims to investigate the university students' attitude towards healthy lifestyle by examining their knowledge toward healthy eating and exercising as a major indicator of practicing healthy lifestyle. A pilot study of 94 students of Universiti Utara Malaysia showed that there were differences between gender, race, and year of study affects the knowledge on of nutrition and exercise benefits. The finding also showed that there was still a loophole in managing healthy lifestyle among university students to ensure that the production of a healthy human capital for the nation.